Uma ferramenta da apoio à engenharia reversa orientada a objetos de legados - FAROOL - Prado, Milene (2003)
This project objectives the development of a support tool to the reverse engineering process for procedimental legacy systems implemented in COBOL, in order to be facilitating their recovery. The FAROOL (Ferramenta de Apoio à engenharia Reversa Orientada a Objetos de Legados) is a guide to software engineers in the reverse engineering process that is based on pre-defined heuristics, so that guided models to the objects are obtained from systems implemented in COBOL. FAROOL addresses two phases, in special, in the process of object guided reverse engineering. The first phase is the Elaboration of the MASA (Modelo de Análise do Sistema Atual, when a legacy systems model of pseudoguided objects is created. The second phase is of MAS Elaboration (Modelo de Análise do Sistema), when a totally model of guided objects is create, being based on the previous model (MASA). By applying the FAROOL, the software engineers are guided so that the reverse engineering process is materialized. First, the preparation of the system is made, aid of the Legacy Aid CASE tool, integrated to the FAROOL tool through macros.They follow the determination of the candidates classes, of the candidates attributes and of the candidates methods of the MASA model, that can become candidates to the class, to the attributes and to the methods, respectively, of the MAS model. Special heuristics are followed for the confection of the relationships between the candidate class in the model of guided objects. All the information are stored in a relational database, facilitating to the task of the software engineer in the reverse engineering process. The Delphi environment; the relational database Interbase; and the Legacy Aid tool were used in the elaboration of the FAROOL.